Relating snowfall patterns over the central and eastern U.S. to infrared imagery of extratropical cyclone comma heads - Van Cleave, Darren T., author (Colorado State University. Libraries, 2009)
Geostationary satellite imagery is a valuable tool in the analysis and forecasting of a multitude of weather phenomena; in this study, it is applied to wintertime snowfall forecasting. It has been noted that the pattern of cloudiness seen in the comma heads of extratropical cyclones observed with Geostationary Operational Environmental Satellite 10.7 μm imagery may be related to the swath of snowfall deposited by these cyclones as they affect eastern two-thirds of the United States. This study relates that imagery to snow swaths by categorizing extratropical cyclones. In an examination of 24 such cases spanning the last 13 years, three broad categories of cloud-top patterns emerged, each representing 8 of the 24 total cases. The first is the classic comma-head shape, for which there is a contiguous cloud shield covering both the comma head and the frontal zone; this is termed the classic category. In this category, the brightness temperatures within the cloud shield over the comma head are roughly the same as those over the frontal zones. The second category is characterized by a comma head which is distinct (in a brightness temperature sense) from the frontal cloud band; this is called the separated category. In these cases, the brightness temperatures over the cloud head indicate warmer cloud-top temperatures adjacent to the frontal zone. The third category is a separated comma head with cloud-top temperatures in the comma head warmer than in the frontal zone; this is referred to as the warm-separated category. It is observed that differences exist in the snowfall swaths occurring in the vicinity of the comma heads for the three categories. North American Regional Reanalysis data is used to determine the differences in storm structures among the three categories which were responsible for the differing cloud patterns. In particular, composite maps and cross sections of various dynamic and thermodynamic fields are presented. It is found that a different jet position among the various cyclone categories creates varying ageostrophic circulations, with the weaker circulations being associated with separated comma heads. In addition, it is discovered that the presence of a trowal (trough of warm air aloft) airstream in the classic cases is connected with the presence of a contiguous cloud shield, whereas its absence in the separated and warm separated cases is associated with the discontinuous comma head. It is shown that the classic cyclones produce a swath of snow co-located with the coldest cloud tops and spread throughout the southern half of the comma head, while the snow swath of the second and third categories is generally in a narrower band located to the southeast of the coldest clouds. Lastly, the warm-separated category is found to be associated a type of storm evolution which leads to strong cyclogenesis.
Keywords: cyclone forecasting; United States; satellite meteorology; snow measurement